The analogue of the Mahler—Sprindžuk’s theorem for the polynomials in (x, y) of third degree. (II) - Sliesoraitienė, R. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Р. Слесорайтене. Теорема Малера—Спринджука для некоторых полиномов третьей степени от двух переменных. (II) R. Sliesoraitienė. Malerio—Sprindžiuko teoremos analogas trečio laipsnio dviejų kintamųjų polinomams. (II)